Urban violence in the Middle East: changing cityscapes in the transition from empire to nation state (Space and place; volume 14) - Freitag, Ulrike; Fuccaro, Nelida; Ghrawi, Claudia; Lafi, Nora (Space and place, 2015)
Covering a period from the late eighteenth century to today, this volume explores the phenomenon of urban violence in order to unveil general developments and historical specificities in a variety of Middle Eastern contexts. By situating incidents in particular processes and conflicts, the case studies seek to counter notions of a violent Middle East in order to foster a new understanding of violence beyond that of a meaningless and destructive social and political act. Contributions explore processes sparked by the transition from empires — Ottoman and Qajar, but also European — to the formation of nation states, and the resulting changes in cityscapes throughout the region.